Jenis Evaluasi Pembelajaran Pendidikan Agama Islam - Risnawati Risnawati; Miftahir Rizqa; Anggi Maharani Agustina; Nadhila Mastura; Wil Qadri; Radhiatul Husni (Journal Education And Islamic Studies, 2023)
This research aims to examine the types of evaluation that can be carried out by educators to determine students' cognitive and non-cognitive competencies. The method used in this research is library research in which the main data source is obtained from books, articles and scientific journals related to types of learning evaluations in Islamic religious education. The result of this research is to find out the types of learning evaluations for Islamic religious education that can be used to improve the teaching and learning process that is currently being carried out or has already been carried out.